How many valid Pleurosicya (Teleostei: Gobiidae) species are known from the Red Sea? - Goren, Menachem; Bogorodsky, Sergey V.; Rothman, Shevy B-S. (Zootaxa, 2023)
Four species of the gobiid genus Pleurosicya are reported from the Red Sea: P. bilobata, P. mossambica, P. plicata, and P. prognatha. Pleurosicya bilobata is reported as a new record for the Red Sea based on underwater photographs taken from a seagrass area at Dahab, Egypt, Gulf of Aqaba. A previous Red Sea record of P. micheli, a species occurring from Indonesia to French Polynesia, is based on a misidentification of P. mossambica and can be excluded as the Red Sea species. Phylogenetic COI barcode analysis showed that the genetic distance between Red Sea population and Western Indian Ocean specimens of P. mossambica is low, confirming the synonymy of P. sinaia, described from the Red Sea, with P. mossambica. Furthermore, phylogenetic analysis demonstrated that specimens from the western Pacific under the name P. mossambica are genetically distinct and may represent an undescribed species. Brief descriptions accompanied with underwater photographs are provided for four species of Pleurosicya from the Red Sea.